1997
DOI: 10.2307/2266147
|View full text |Cite
|
Sign up to set email alerts
|

Standing Crop and Animal Consumption of Fungal Sporocarps in Pacific Northwest Forests

Abstract: Although fungal fruiting bodies are a common food supplement for many forest animals and an important dietary staple for several small mammals, changes in their abundance and consumption with forest succession or disturbance have not been quantified. Above-and belowground fungal fruiting bodies (epigeous and hypogeous sporocarps) were sampled for 46 mo in managed-young, natural-mature, and old-growth western hemlock (Tsuga heterophylla) stands in Washington State. Screen exclosures were placed over the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 35 publications
(73 reference statements)
5
64
2
1
Order By: Relevance
“…Attempts were made to locate sporocarps in the field sites, but none were recovered. This was not surprising due to the hypogeous nature of the sporocarp, sporadic fruiting, removal of most sporocarps by mammals (North et al 1997) and the putative rarity of this species in eastern forests. This fungal species was not frequent in the soil spore banks of eastern white pine forests with or without pinedrops, but was less frequent in the latter.…”
Section: Discussionmentioning
confidence: 95%
“…Attempts were made to locate sporocarps in the field sites, but none were recovered. This was not surprising due to the hypogeous nature of the sporocarp, sporadic fruiting, removal of most sporocarps by mammals (North et al 1997) and the putative rarity of this species in eastern forests. This fungal species was not frequent in the soil spore banks of eastern white pine forests with or without pinedrops, but was less frequent in the latter.…”
Section: Discussionmentioning
confidence: 95%
“…We sampled soils for truffles using the same size and number of plots as the methodology of Luoma et al (1991), which has been adopted by others for comparative studies (North et al, 1997;Waters et al, 1997;Smith et al, 2002). We systematically located 25 4 m 2 circular plots 40 m apart on an 8 Â 8 or 7 Â 9 grid used for trapping flying squirrels.…”
Section: Trufflesmentioning
confidence: 99%
“…Much is known about EMF diversity (Fogel and Trappe, 1978;Luoma et al, 1991;North et al, 1997;Colgan et al, 1999;Smith et al, 2002) and rodent mycophagy (Fogel and Trappe, 1978;Maser et al, 1986;Carey, 1995;Carey et al, 1999) in wet Douglasfir forests in the Pacific Northwest (PNW) west of the Cascade Range crest. Others have studied relatively mesic mixed-conifer fir forests in the interior West Rosentreter et al, 1997;Currah et al, 2000;Pyare and Longland, 2001); but, there is scant data for dry low-elevation forests dominated by ponderosa pine (Pinus ponderosa), dry Douglas-fir (Pseudotsuga menziesii), or dry grand fir (Abies grandis) plant associations outside of Arizona (States and Gaud, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that the sticky gleba of L. mokusin was rarely attached to the body of A. maritima, in accordance with the hypothesis that Dictyophora spores are largely dispersed via guts of visitors rather than by adhering to insect bodies (Tuno, 1998). Advantages of spore dispersal by animals may include extension of dispersal range, access to new nutrient sources, and enhancement of gamete transfer for mating (Ingold and Hudson 1993;North et al 1997;Steinebrunner et al 2007). We found that L. mokusin provides food in the form of gleba to the earwig A. maritima, which may excrete about 1.18×10 7 spores of L. mokusin per day (far more than the numbers, ca.…”
Section: Discussionmentioning
confidence: 99%